The Naming of Women in Early Roman Liburnia and the so-called "Female Praenomina" (Archaeologia Adriatica, 2008)
The article discuuses the system of naming women in early Roman Liburnia. Particular attention is paid to formulas where the personal name is in the first position in naming a woman (the so-called female "praenomina"), in front of the indigenous collective name or in front of the Latin gentilicium. Such a system of naming was autochthonous among the Liburnians, and was a reflection of the structure in which a female was experienced as a discrete individual, and in which women were more or less equal to men, and hence their naming was carried out in the same manner as for men.
Keywords: Liburnian anthroponomy; Roman anthroponomy; "female praenomina"